Competency Teaching in Basic Education: proposal for a content assessment tool (Research, Society and Development, 2020)
Competence is defined in the Common National Curricular Base (BNCC) as the mobilization of knowledge, skills, attitudes and values to solve complex demands of everyday life however, it does not point out how to assess competences in basic education.  In this job, through a case study and and qualitative approach, aims to propose a content evaluation instrument,  for elementary school students at a college that belongs to the federal public school system, in a multidisciplinary way. The results demonstrate that competences can be measured using a simple, objective and replicable instrument.